2019
DOI: 10.3126/banko.v29i1.25152
|View full text |Cite
|
Sign up to set email alerts
|

Status and distribution of Red Panda (Ailurus fulgens fulgens) in Simsime community forest of Papung VDC of Taplejung district, Nepal

Abstract: Red Panda (Ailurus fulgens fulgens), globally an endangered species of Himalaya, were studied in Simsime community forest of Papung Village Development Committee (VDC) in Taplejung district. It was carried out to assess status, habitat characteristics and threats to Red Panda. Three transects were laid out along the contours and their total length was 2200 m. The altitude of these transects varied from 2800–3400m. While moving along the transect line, the signs such as pellets, footprints and nests of Red Pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The average relative abundance (ER= 0.92 signs/km) of Himalayan Red Panda scats were found lower than the Taplejung District of eastern Nepal where an average ER was observed to be 1.36 signs/km (Lama 2019). This might be due to profligate propagation of the shrub layer and ground layer that had reduced the detection rate of indirect signs (Hemami & Dolmen 2005).…”
Section: © Bhim Bahadur Shahimentioning
confidence: 99%
“…The average relative abundance (ER= 0.92 signs/km) of Himalayan Red Panda scats were found lower than the Taplejung District of eastern Nepal where an average ER was observed to be 1.36 signs/km (Lama 2019). This might be due to profligate propagation of the shrub layer and ground layer that had reduced the detection rate of indirect signs (Hemami & Dolmen 2005).…”
Section: © Bhim Bahadur Shahimentioning
confidence: 99%
“…(Chaudhary, 2001). According to Lama (2019), the main threats to red pandas in Nepal's Simsime Community Forest in Papung VDC of Taplejung district are grazing and bamboo cutting.…”
Section: Threatsmentioning
confidence: 99%
“…Red pandas are said to like locations with dense forest (tree canopy cover of over 30%), a lot of bamboo cover (>37%), bamboo height (2.9 m), and are located within 100 to 200 meters of water sources (Dorji et al, 2012;Pradhan et al, 2001a). These creatures have been discovered in regions with yearly rainfall averaging 3500 millimeters and temperatures between 10 and 25 degrees Celsius (Lama, 2019). Even though they are typically thought of as a solitary species, during the breeding season, they are often seen in small groups, possibly with their mothers and young (Hu, 1991;Robert et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of research publication increased between 2013 and 2020 in Nepal (n= 33), Bhutan (n= 6), and India (n= 15) with the majority of the research papers (n= 17) focusing on various aspects of the species habitat (Bhatta et al, 2014;Chakraborty et al, 2015;Kandel et al, 2015;Dendup et al, 2018;Bista et al, 2019;Dendup et al, 2020) followed by population (n= 13) Bashir et al, 2019;Lama, 2019), 11 papers published on different aspects of impact on the species (Sharma et al, 2014;Acharya et al, 2018;Bhattarai, 2019;Bista et al, 2020;Lama et al, 2020), four papers published on disease (Lama et al, 2015;Shrestha and Maharjan, 2015;Shrestha and Maharjan, 2017) and two papers published on the genetics of the species in India (Kumar et al, 2016;Dalui et al, 2020). Three papers were published covering the species in multiple countries; two of them on habitat covering the overall range of A. fulgens and one on genetics in the mountains of Nepal and China (Hu et al, 2020).…”
Section: Research Trends On Ailurus Fulgensmentioning
confidence: 99%
“…In different studies across the range countries (Liang et al, 2007;Gyeltshen, 2010;Bista and Paudel, 2013;Chalise, 2013;Wangchuk, 2013;Mallick, 2015;Dendup et al, 2017;Bashir et al, 2019;Bhattarai, 2019;Ghimire et al, 2019;Tobgay and Mahavik, 2020) livestock pressure and grazing have been identified as critical issues for the survival of A. fulgens. Likewise, bamboo loss, unmanaged harvesting, and bamboo flowering are other key threats to A. fulgens (Bista and Paudel, 2013;Sharma et al, 2014;Dendup et al, 2017;Drukpa, 2018;Bashir et al, 2019;Ghimire et al, 2019;Lama, 2019).…”
Section: Conservation Threatsmentioning
confidence: 99%